2010
DOI: 10.1186/1748-717x-5-34
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the fullerene compound DF-1 as a radiation protector

Abstract: BackgroundFullerene compounds are known to possess antioxidant properties, a common property of chemical radioprotectors. DF-1 is a dendrofullerene nanoparticle with antioxidant properties previously found to be radioprotective in a zebrafish model. The purpose of this study was to evaluate the radioprotective effects of DF-1 in a murine model of lethal total body irradiation and to assess for selective radioprotection of normal cells versus tumor cells.MethodsIn vitro radioresponse was evaluated with clonogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 36 publications
0
13
0
Order By: Relevance
“…Treatment with A(1–7) in this study starting 48 h after TBI and where no bleeding was done, improved survival at all doses of A(1–7) tested (Figure 10). The LD 50/30 for survival after TBI is in the range of 7.75–8.3 GY in this strain (Day et al 2008, Brown et al 2010). We found that 40% of TBI mice succumbed by 30 days if no A(1–7) was administered and this is consistent with the data of Brown and of Day mentioned above (or 60% of mice survived).…”
Section: Recovery Of Circulating Formed Elementsmentioning
confidence: 76%
“…Treatment with A(1–7) in this study starting 48 h after TBI and where no bleeding was done, improved survival at all doses of A(1–7) tested (Figure 10). The LD 50/30 for survival after TBI is in the range of 7.75–8.3 GY in this strain (Day et al 2008, Brown et al 2010). We found that 40% of TBI mice succumbed by 30 days if no A(1–7) was administered and this is consistent with the data of Brown and of Day mentioned above (or 60% of mice survived).…”
Section: Recovery Of Circulating Formed Elementsmentioning
confidence: 76%
“…The process includes decrease of ROS level, inhibition of radiation-induced apoptosis and cells necrosis, DNA damages, oxidative stress. However, the process is not selective, because no difference between modest protective effect of the dendro-fullerene on normal fibroblasts (dose modifying factor=1.1 [99]) and on tumor cells was observed in vivo. LD 50/30 for mice, received 300 mg/kg of the dendro-fullerene before irradiation, was equal to 10.09 Gy in comparison with 8.29 Gy for control group.…”
Section: Ionizing Radiation and Fullerenesmentioning
confidence: 99%
“…The hallmark late effect of radiation exposure in several experimental animals is fibrosis, which is often permanent (Han et al, 2006;Lee et al, 2009;Flechsig et al, 2010;Qiu et al, 2011;Gorshkova et al, 2012;Cho et al, 2013;Ding et al, 2013;Horton et al, 2013). A number of chemical agents showed mitigation to radiation-induced injuries in animal models (Gandhi and Nair, 2004;Parihar et al, 2007;Thotala et al, 2009;Brown et al, 2010;Gao et al, 2012;Kma et al, 2012;Peebles et al, 2012;Alok et al, 2013;Copp et al, 2013).…”
Section: Lakhan Kmamentioning
confidence: 99%